The Role of Laboratory Measurements on D-dimer Level in Patients with COVID-19: A Retrospective Study - Abdulah, Deldar Morad; Ahmed, Ghazwan Fawzi; Ismaeel, Qais Ibraheem (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Inflammation may raise the concentration of D-dimer level in COVID-19 patients. There is no consensus on the role of inflammation on the D-dimer level in the literature. We aimed to examine the role of inflammation in D-dimer level in COVID-19 patients.Methods: The patients who were suspected of COVID-19 disease were referred by one of the medical doctors to a private medical lab between 1 July and 30 November 2020. The patients with COVID-19 infection were diagnosed using a combination of IgG and IgM antibodies. The confirmed laboratory patients were considered cases (n=204) and others as healthy controls (n=440) in this case-control investigation.Results: In this study, the patients were older compared to the healthy controls; 54.5 vs. 51.5 years; P=0.0251. The patients had a significantly higher concentration of D-dimer (483.5 vs. 318 µg/ml; elevated prevalence: 48.53% vs. 22.95%; P